HUBUNGAN PERAWATAN PAYUDARA DENGAN KELANCARAN ASI PADA IBU NIFAS - Damanik, Veronica Anggreni (Jurnal Keperawatan Priority, 2020)
ASI has the most complete nutritional composition and is ideal for infant growth and development during the first 6 months. However, only 39 percent of all babies in the world get exclusive breastfeeding and there are still many mothers who are less successful at breastfeeding or stop breastfeeding early. Based on Indonesia's Health Profile in 2016 the percentage of breastfeeding in Indonesia from 0-6 months infants was 29.5%. This study aims to determine the relationship of breast care with the smoothness of breast milk in postpartum mothers at the Poskeskel Clinic in Medan. The design of this study was an analytic survey with cross sectional approach. The sampling technique is total sampling, a sample of 40 respondents. The research was conducted at the Poskeskel Clinic in Medan and in July-September 2018. Data analysis used was the Chi-Square test. The results of this study indicate that the p-value is 0.004 (<α 0.05), which means there is a relationship between breast care and the smoothness of breast milk in postpartum mothers. The conclusion is that there is a relationship between breast care, and the smoothness of breastfeeding in parturition mothers. It is advisable for postpartum mothers to care for the breasts after the baby is born and postpartum at least 2 times a day regularly and it is advisable for health workers to conduct counseling and demonstrate the steps of breast care for pregnant and lactating women so that the production of ASI is plenty and smooth.